Processes of transformation of morphological dimensions among youth category soccer players caused by situational training - Colakhodzic, E.; Rado, I.; Alic, H. (Homosporticus, 2009)
The aim of this research was to determine quantitative changes of morphological dimensions among soccer players aged 12-15 (n=75), caused by programmed situational training. The program lasted six months, containing 72 training units based on situational training model and eight league games. The programme was developed on a modern vision of soccer training with younger categories which is promoted by the UEFA, and it is based on simplification and soccer problem solving through game (Michels, 2001). Training process is structured so that playing and exercise are combined, and in each stage situational working method was applied. The subject of the research included transformation processes of morphological characteristics among soccer players aged 12-15, with the aim of determining the effects of programmed training exercise on the dimensions covered by the research. Quantitative changes of morphological dimensions which occurred due to the effects of the six-month programme were analysed through canonical discriminative analysis under the model of differences. Acquired results show that a statistically significant change occurred within the period of two measurements. Greatest contribution to the discriminative function are provided by two variables for under-skin fat tissue measurement of the lower leg (AKNP), the upper leg (AKNB) and stomach (AKNT), transversal dimensionalities of the skeleton diameter of the knee (ADIKO), diameter of the foot joint (ADISZ) and one measure of the longitudinal dimensionality of the skeleton, the length of the foot (ADUS). It can be concluded that situational six-month training model positively affected the transformation of almost all morphological dimensions, especially of the variables manifested in the under-skin fat tissue.